PHARMACOLOGICAL EVALUATION OF SPHAERANTHUS INDICUS LINN. USING ALBINO RATS. - Robert, J.; Louis, C.; Ayyavoo, M. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Sphaeranthus indicus Linn. is a plant of the Compositae family, which has anti-inflammatory properties. Inflammation due to the infiltration of macrophages and neutrophils is a key event in the mediation of the toxic responses elicited by the notorious hepatotoxicant. Flavonoids and polyphenols isolated from Sphaeranthus indicus, owing to their antioxidant, tissue regenerating and free-radical scavenging properties, can cure the oxidative damage caused by the activation of the drug and its toxic metabolites. The hepatoprotective effect of the bioactive principles isolated from Sphaeranthus indicus was evaluated in rats by using serum and tissue markers that signified acetaminophen hepatotoxicity. Serum parameters were evaluated in acetaminophen intoxicated rats to check for liver-specific markers such as AST, ALT, ALP and they were found to be elevated in the serum signifying liver damage. Treatment with the active principles of Sphaeranthus indicus significantly lowered these markers and showed regeneration of liver tissue, as revealed by histopathological studies along with the restoration of the activities of the antioxidant enzymes such as glutathione peroxidase (GPx), reduced glutathione (GSH), superoxide dismutase (SOD) and catalase. Enhanced serum bilirubin and diminished protein levels were observed in the intoxicated group, whereas the reverse trend was observed in the treated groups. In addition, as acetaminophen is capable of causing kidney damage by mechanisms identical to those of the liver, the conditions of the kidney was also monitored by analyzing serum urea, uric acid and creatinine levels. The results also highlighted the nephroprotective role of the active principles of Sphaeranthus indicus.